2010
DOI: 10.1007/s11128-009-0155-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing quantum channels via magic squares game

Abstract: We study the effect of quantum memory in magic squares game when played in quantum domain. We consider different noisy quantum channels and analyze their influence on the magic squares quantum pseudo-telepathy game. We show that the probability of success can be used to distinguish the quantum channels. It is seen that the mean success probability decreases with increase of quantum noise. Where as the mean success probability increases with increase of quantum memory. It is also seen that the behaviour of ampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…systems [37] and can be used to study the effect of decoherence in such systems [38,39,40,41,42]. In this connection, different damping channels can be used as a theoretical framework to study the influence of decoherence in quantum game problems.…”
Section: Effect Of Decoherencementioning
confidence: 99%
“…systems [37] and can be used to study the effect of decoherence in such systems [38,39,40,41,42]. In this connection, different damping channels can be used as a theoretical framework to study the influence of decoherence in quantum game problems.…”
Section: Effect Of Decoherencementioning
confidence: 99%
“…MSG is played by two players against a referee and utilizing a pre-shared quantum system of 4 qubits in a specific pure entangled state, players can win the game with unit probability, while players equipped only with classical resources can achieve a winning probability at most 8/9 [18,19]. In practical applications, however, due to inevitable interactions of the state with the environment [20][21][22], or even accelerating players [23], the entanglement of the state may decrease considerably, leading to the decrease of the winning probability even far below the classical limit. On the other hand, Pawela et al have recently showed that in spite of decoherence, the winning probability can be enhanced if each party performs local operations (determined by semi-definite programming) to their qubits [24].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum games may provide a feasible platform for implementing quantum information processing in physical systems [27] and can be used to probe the influence of decoherence in such systems [6,[28][29][30][31]. In this connection, quantum channels provide a natural theoretical framework for the study of decoherence in noisy quantum communication systems.…”
Section: Introductionmentioning
confidence: 99%